(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Personality pertains to the different patterns of behaviour, cognitive processes, and emotional responses that distinguish individuals. It is composed of three primary components: physiological, psychological, and environmental factors. Personality is referred to as ’Prakriti’ expressing an individual’s intrinsic qualities impacted by their genetic physical and mental composition, in the domain of Ayurveda. The predominant Doshas present during conception, as well as those within the womb, ultimately shape a person’s Prakriti. The Prakriti constitution signifies the unique equilibrium that exists between the Sharira (body) and the Manas (mind). Manasa Prakriti or the psychic expression or constitution, is the inherent mental disposition resulting from the union of Sukra (semen), Shonita (ovum), and Atma (soul). According to Ayurveda, the relative dominance of the three principal mind components referred to as Trigunas: Satwika (purity), Rajasika (movement), and Tamasika (inertia and dullness), also known as Maha prakriti, shapes a person’s psychological constitution. Identifying and encouraging personal development, enhancing interpersonal skills, and nurturing leadership qualities are all benefits of assessing an individual’s Manasa prakriti. It also plays an important role in sustaining health and recommending appropriate therapeutic procedures. Furthermore, the prognosis is determined by an individual’s Manas Prakriti type. In this review, an attempt is made to explore the Ayurvedic concept of Manasa Prakriti in light of contemporary temperament theory and personality disorders.